Implementation of the Pancasila Student Profile Strengthening Project (P5) Based on the Lilian Katz Model to Improve School Readiness of 5-6 Year Old Children - Oktarina Dwi Handayani; Hilda Ayu Nur Santi (Universitas Al-Hikmah Indonesia, 2025)
This study aims to analyze the Development of the Pancasila Student Profile Strengthening Project (P5) Based on the Lilian Katz Model in Improving School Readiness for Children Aged 5-6 Years. The method used was a quasi-experiment with a pretest-posttest control group design , involving 30 children as the experimental group and 15 children as the control group. The experimental group received project-based learning with the Lilian Katz model, while the control group used conventional methods. The research instrument was a child development assessment questionnaire covering aspects of cognition and general knowledge, language, social-emotional, physical motor skills, and learning approaches. Data were analyzed using the N-Gain Score test to measure the increase in school readiness. The results showed that the experimental group experienced a more significant increase than the control group, the experimental group with an average N-Gain of 0.76 (high category) while the control group was 0.63 (moderate category). These findings indicate that project-based learning with the Lilian Katz model involving exploration, collaboration, and reflection is more effective in preparing children holistically to enter elementary education. In conclusion, the Lilian Katz Model in P5 can be an innovative and effective learning strategy to improve early childhood school readiness. This study recommends the implementation of a project-based approach in the PAUD curriculum to support optimal child development.